MEKANISME PENYELESAIAN SENGKETA KONSTRUKSI MENURUT UNDANG-UNDANG NOMOR 2 TAHUN 2017 TENTANG JASA KONSTRUKSI - Mas Agus Priyambodo (IBLAM Law Review)
In essence, construction projects arise because of the convergence of two interests.On the  one hand, there is a demand (demand) from the Service User, on the other hand the  Service Provider offers its service (offer). Therefore, law number 2 of 2017 concerning  Construction Services in Article 1 Paragraph (5) and (6) defines Service Users as owners  or employers who use Construction Services, while Service Providers are providers of  Construction Services. Construction is a very complex industry, this is because in construction projects there are multiple disciplines and dealing with many people who  have their own interests. This condition also opens up opportunities for greater disputes. Disputes in construction work contracts or construction disputes are events that  sometimes arise and cannot be avoided in the execution of the contract. The causes of  this also vary from both internal and external factors. The problem in this paper is howto  resolve construction disputes according to law number 2 of 2017 concerning construction  services. The research used is normative legal research, which relies on secondary data as  the main data source. The results showed that after the issuance of Law no. 2/2017 concerning Construction Services, construction disputes must first be resolved through  deliberation for consensus. If the disputing parties do not find an agreement, then the  settlement is taken through the stages ofdispute resolution as regulated in the construction  work contract. Then if the dispute resolution is not stated in the construction work  contract, then the parties with written approval will regulate the dispute resolution procedure chosen.